Implementation of education at GMIT elementary schools in mainland Timor: A CIPP model evaluation study - Fredrik Abia Kande; Jollyanes P. Ledo; June A. Jacob; Anggreini D. N. Rupidara; Eltina Maromon (Universitas Negeri Yogyakarta, 2022)
This article aims to evaluate the quality of education at Evangelical Protestant Church in Timor (GMIT) elementary schools (ES), henceforth shortened to GMIT ES, in mainland Timor. The evaluation method is used with the evaluation model of CIPP (context, input, process, and product). The research sample consists of 173 headmasters of GMIT ESs in mainland Timor. The data collection is done by using a questionnaire. The data analysis uses descriptive statistics (percentage calculation technique). The results show that the quality of the context, input, process, and product can be described as follows: the context is in the sufficient category, the input is in the sufficient category, the process is in a good category, and the product is in a good category. Overall, the quality of the implementation of education at GMIT ESs in mainland Timor is in the sufficient category. The supporting factors are the attention from the government, the church, and the Christian Education Foundation (Yapenkris) with varying weights, and the commitment of the teachers who understand their duties as part of the ministry. The inhibiting factors are related to the minor role of Yapenkris and the GMIT congregations, the lack of welfare for teachers, and the absence of a governance model for schools under GMIT.